2016
DOI: 10.1097/mpg.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Optimal Fatty Acid Absorption in Preterm Infants

Abstract: Objectives To quantify absorption coefficients of specific fatty acids in preterm infants as a function of diet, formula (F) or breast milk (BM), and postnatal age; and, to identify the fatty acid structural characteristics that determine optimal fatty acid absorption. Methods Fatty acids from dietary and fecal samples were extracted and quantified by gas chromatography-mass spectroscopy. Fatty acid absorption coefficients (FA-CFAs) were calculated by comparing the total amount of fatty acids supplied by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
1
13
1
1
Order By: Relevance
“…Some authors have indicated that absorption of FFAs is worse in formula-fed babies, while in our study we did not find differences in FFA levels regarding feeding protocol [18]. Martin et al [19] noted that preterm babies did not improve FFAs absorption during the first 2 months of life. In our study, in preterm infants, we reported a decrease in plasma FFA concentrations in the second month of life when compared to the results obtained after birth, independent from feeding protocol, as well as lower than in the control group.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Some authors have indicated that absorption of FFAs is worse in formula-fed babies, while in our study we did not find differences in FFA levels regarding feeding protocol [18]. Martin et al [19] noted that preterm babies did not improve FFAs absorption during the first 2 months of life. In our study, in preterm infants, we reported a decrease in plasma FFA concentrations in the second month of life when compared to the results obtained after birth, independent from feeding protocol, as well as lower than in the control group.…”
Section: Discussioncontrasting
confidence: 48%
“…Just after birth, mobilization of FAs from these stores is observed as an increase in plasma FFA concentrations [19]. Preterm infants with low birth weight had reduced endogenous lipid resources, reflected as a lower plasma FFA concentration, also observed in this study, when compared to full-term babies just after birth [19]. It has been previously shown that preterm infants also had developmental deficiencies in enteral fat digestion and absorption, leading to a malabsorptive state [18].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, other lipid components, such as the triacylglycerol‐, phospholipid‐, and cholesterol ester backbones, make up a minor part of the total fat content . Finally, all FAs were assumed to be fully absorbed, although the true bioavailability in preterm infants is reported to be in the range of 85%–100% depending on FA species . Birth weight was used when normalizing milk and parenteral lipid emulsion intake to mg per kg body weight during the first 2 weeks of life.…”
Section: Methodsmentioning
confidence: 99%
“…Along with essential fatty acids, linoleic acid (LA) and alpha linoleic acid (ALA), as well as omega-6 fatty acids such as arachidonic acid (ARA), PUFAs also contribute to a number of physiological functions, including that of immunomodulation [4,5]. However, PUFAs are poorly digested and thus poorly absorbed in preterm infants due to the immaturity of the gastrointestinal system and (developmental) exocrine pancreatic insufficiency [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%